Assessment of pap smear and colposcopic findings in patients with vaginal discharge - Nagajan Bhadarka; Nimish Pandya; Satyam Joshi (Barpeta Obstetrics and Gynaecological Society, 2019)
Aim: Present study was performed with an aim to see the types of vaginal discharge with the pap smear and colposcopic findings. Material and Methods: This cross-sectional study was conducted in 68 women attending outpatient department (OPD) of Obstetrics and Gynaecology. Types of vaginal discharge with pap smear, colposcopy findings such as normal impression, inflammatory changes, cervical intraepithelial neoplasia and invasive carcinoma were observed. Results: Among the study group, majority of them 51.9% came to the hospital with history of vaginal discharge which is thick, white and 42.4% gave history of thin watery vaginal discharge. In the present study 14.5% gave history of post coital bleeding and 22.2% women gave history of post menopausal bleeding. Cervical biopsy was taken in all the patients, of which 15.7% had no evidence of malignancy, 30.9% had CIN I,16.10% had CIN II, 19.7% had CIN III, 8.4% had CIS, 7.1% were found to have squamous cell carcinoma, 1.4% had adenocarcinoma. Conclusion: Carcinoma cervix has a long pre invasive state. Excessive vaginal discharge for long duration is to be assessed for cervical pathology.